Pengembangan Instrumen Assessment as Learning (AaL) pada Materi Sistem Persamaan Linear Tiga Variabel Di Kelas X SMA - Nurwati Djam'an; Maulidiyah Ananda Nasrul; Ja’faruddin (Universitas Dr. Soetomo, 2026)
Abstract This study aims to (1) develop an Assessment as Learning (AaL) instrument for the topic of systems of linear equations in three variables for Grade X senior high school students, and (2) determine the validity and reliability of the developed Assessment as Learning instrument for the same topic. The research employed Research and Development (R&D) design. The participants consisted of 36 Grade X students of SMAN 2 Gowa and two lecturers who served as expert validators. At the same time, the research object was the Assessment as Learning (AaL) instrument for the topic of systems of linear equations in three variables. The instrument comprised self-assessment, teacher-assessment, and peer-assessment sheets, along with their rubrics covering knowledge, attitudes, and skills, and formative and summative individual test items in multiple-choice format. The results indicate that: (1) the development process of the Assessment as Learning (AaL) instrument was carried out through the stages of specification development, instrument writing, instrument review, instrument revision, instrument try-out, instrument analysis, and instrument assembly; and (2) the developed Assessment as Learning (AaL) instrument for the topic of systems of linear equations in three variables for Grade X senior high school students, including self-assessment sheets, teacher assessment sheets, peer assessment sheets, individual test rubrics, individual test items, and summative multiple-choice test items was found to be valid and reliable. Keywords: Assessment as Learning (AaL); Development Procedure; Systems of Linear Equations in Three Variables; Validity; Reliability. Abstrak Penelitian ini bertujuan untuk (1) mengembangkan instrumen Assessment as Learning (AaL) pada materi sistem persamaan linear tiga variabel bagi siswa kelas X SMA dan (2) mengetahui validitas dan reliabilitas instrumen Assessment as Learning yang dikembangkan pada materi sistem persamaan linear tiga variabel di kelas X SMA. Jenis penelitian yang digunakan adalah penelitian pengembangan research and development (R&D). Subjek dalam penelitian ini adalah peserta didik kelas X SMAN 2 Gowa sebanyak 36 orang dan 2 dosen yang bertindak sebagai validator, sedangkan objek dari penelitian ini adalah instrumen Assessment as Learning (AaL) pada materi sistem persamaan linear tiga variabel di kelas X SMA yang terdiri dari lembar penilaian diri, lembar penilaian guru terhadap peserta didik, lembar penilaian antar teman beserta rubriknya dalam aspek pengetahuan, aspek sikap serta aspek keterampilan, soal tes individu formatif, dan soal tes individu sumatif dalam bentuk pilihan ganda. Hasil penelitian menunjukkan bahwa: (1) Proses pengembangan instrumen Assessment as Learning (AaL) dilaksanakan dengan tahapan penyusunan spesifikasi, penulisan instrumen, penelaahan instrumen, memperbaiki instrumen, uji coba instrumen, analisis instrumen, dan perakitan instrumen; (2) Hasil pengembangan instrumen Assessment as Learning (AaL) pada materi sistem persamaan linear tiga variabel di kelas X SMA terdiri dari lembar penilaian diri, lembar penilaian guru terhadap peserta didik, lembar penilaian antar teman, rubrik soal tes individu, soal tes individu, dan soal tes individu sumatif dalam bentuk pilihan ganda dinyatakan valid dan reliabel. Kata Kunci: Assessment as Learning (AaL); Prosedur Pengembangan; Sistem Persamaan Linear Tiga Variabel; Validitas dan Reliabilitas.